The Edinburgh companion to fin-de-siècle literature, culture and the arts - Guy, Josephine (Edinburgh University Press, 2017)
The late nineteenth-century fin de siècle has proved an enduringly fascinating moment in literary and cultural history. It is associated with the emergence of intriguing figures—such as the 'new woman' and 'uranian'; with contradictory impulses—of decadence and decay on the one hand, and of experiment and renewal, on the other; as well as with unprecedented intercultural exchange, especially between Britain and France. The 22 newly-commissioned essays collected here re-examine some of the key concepts taken to define the fin de siècle, while also introducing hitherto overlooked cultural phenomena into the frame, such as the importance of humanitarianism. The impact of recent research in material culture is explored, particularly how the history of the book and the history of performance culture is changing our understanding of this period. A wide range of cultural activities is discussed—from participation in avant-garde theatre to interior decoration and from the writing of poetry to political and religious activism. Together, the essays provide new scholarly insights into British fin de siècle and enrich our understanding of this complex period, while paying particular attention to the importance of regionalism.